Point-of-care troponin testing and management of patients with acute coronary syndrome: a systematic review. (2nd January 2020) - Du, Huiyun; Chan, So Ting; Wonggom, Parichat; Newman, Peter; Tirimacco, Rosy; Clark, Robyn A.
Abstract : Background: Early identification of acute coronary syndrome is crucial for a patient's likelihood of survival. Point-of-care testing of cardiac troponin is a rapid test of cardiac troponin that can be conducted closer to where clinical care is delivered, with a significant shorter turnaround time. Point-of-care testing of troponin may improve timely diagnosis of acute coronary syndrome. Aim: To examine existing evidence on the effectiveness of point-of-care testing of troponin for acute coronary syndrome management in the emergency department. Methods: A systematic review of randomised controlled trials was conducted across databases, and grey literature. Results: No study evaluated adherence to acute coronary syndrome management guidelines. One of the five studies that assessed length of stay showed a statistically significant reduction ( P =0.035). Two of the three studies that measured time to disposition in emergency department demonstrated statistically significant effects ( P =0.04 vs P =0.05) favouring point-of-care testing of troponin. One study demonstrated statistically significant effects on successful discharge to home from emergency department ( P =0.001). No significant effects were reported for mortality or accuracy. Conclusion: Point-of-care testing of troponin can significantly reduce time to disposition in emergency department and successful discharge home. Translation of this evidence into clinical practice is recommended.